Mobile Communication and Power Engineering Second International Joint Conference, AIM/CCPE 2012, Bangalore, India, April 27-28, 2012, Revised Selected Papers - Das, Vinu V.; Chaba, Yogesh; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book comprises the refereed proceedings of the International Conference, AIM/CCPE 2012, held in Bangalore, India, in April 2012. The papers presented were carefully reviewed and selected from numerous submissions and focus on the various aspects of research and development activities in computer science, information technology, computational engineering, mobile communication, control and instrumentation, communication system, power electronics and power engineering.
Computer science -- Information technology -- Computational engineering -- Mobile communication -- Control and instrumentation -- Communication system -- Power electronics and power engineering.
Keywords: Computer science; Data transmission systems; Computer Communication Networks; Software engineering; Information storage and retrieval systems; Optical pattern recognition; Computer Science; Computer Communication Networks; Input/Output and Data Communications; Computer Applications; Software Engineering; Information Storage and Retrieval; Pattern Recognition